Calcaneal fractures: radiological and CT evaluation and classification systems - Galluzzo, Michele; Greco, Federico; Pietragalla, Michele; De Renzis, Alioscia; Carbone, Mattia; Zappia, Marcello; Maggialetti, Nicola; D’andrea, Alfredo; Caracchini, Giuseppe; Miele, Vittorio (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: The calcaneus, the more lower bone of the body, has the task of supporting the axial load from the weight of the body. Calcaneal fractures represent about 1-2% of all fractures and 60% of the tarsal bones fractures. The articular involvement has been associated with a poor functional outcome. The aim of this work is to describe the radiologic evaluation, the classification systems, the morphological preoperative diagnostic imaging features of calcaneal fractures, highlighting the correlation with the choice of treatment and predictive capacity for the fracture surgical outcome. Methods: A PubMed search was performed for the terms Imaging calcaneus fracture, selecting articles in English language, published in the last two years, where preoperatively diagnostic imaging of fractures of the calcaneus are described.  Case reports have not been included. Results: We have collected a number of data that provide important help in preoperative evaluation of calcaneal fractures, such as the new classification system created by Harnroongroj et al, the association of calcaneal fractures with fractures of other bone structures or soft tissue impairment, the use of calcaneotalar ratio in assessing the length of heel. Conclusions: These data suggest an approach geared to the specific choice of treatment and to improving patient outcomes.